(untitled) (Dhaka University Journal of Science, 2022)
Heat waves (HWs) are an extreme temperature condition that has a direct impact on human lives. In recent years, a large number of people have died all over the world due to hot weather. The purpose of this study is to predict HWs accurately to mitigate the casualties caused by them. Two HW events are selected for this study (Event-1: 0000 UTC of 18 May to 0000 UTC of 25 May 2015, Event-2: 0000 UTC of 05 April to 2100 UTC of 08 April 2015). At first, sensitivity tests have been done using different combinations of physics schemes. Sensitivity of Planetary boundary layer (PBL) and surface layer (SL) schemes combinations (YSU-Revised MM5, YSU-MM5, MYJ-Eta, and ACM2-Revised MM5) and land surface models (RUC, Noah, Noah-MP, and CLM4) are investigated to predict Comfort Index (CI), which is identified by using Physiological Equivalent Temperature (PET). To simulate PET, the primary meteorological variables 2-m air temperature (T2), 2-m relative humidity (rh2), mean radiant temperature (TMRT), wind speed at 10 m (ws10), and cloud cover data have been used. These parameters were simulated by the WRF model using both single and nested domains. The experiments found that the combination of the YSU-MM5 scheme and the Noah land surface model predicted the WRF simulated variables very well. The study also found that the CI exists between the slight heat stress to extreme heat stress and the maximum PET values were found to be 47.6 ºC and 48.5 ºC for Rajshahi and Khulna event respectively. Dhaka Univ. J. Sci. 70(1): 70-78, 2022 (January)